PP.21.34: EXTENSIVE DEVELOPMENT OF A NEW ANTIHYPERTENSIVE STRATEGY. (June 2015) - Mancia, G.; Bakris, G.L.; Laurent, S.; Poulter, N.R.; Lucien, A.; Feldmann, L.
Abstract : Objective: To develop a new single-pill combination comprising a full strategy starting first-line for non-controlled hypertensive patients and to assess its efficacy and safety. This new first-line single-pill strategy is based on three novel and optimized dosages of perindopril arginine/amlodipine: 3.5/2.5 mg, 7/5 mg, and 14/10 mg. Context: Despite the development of novel antihypertensive therapies and evolving clinical practice guidelines, blood pressure control remains suboptimal. Design and method: This single pill was developed in accordance with European Medicines Agency guidelines on clinical investigation of medicinal products in the treatment of hypertension and clinical development of fixed combination medicinal products. The clinical trial program included 4 studies in 7462 patients with documented essential hypertension. Two studies evaluated the efficacy specifically of the first and higher dosages of the single pill, in direct comparison with monotherapies. Two other studies evaluated the strategy in comparison with a classic stepped-care strategy based on angiotensin II receptor blockers. Results: The following efficacy primary end points were met across four studies: The superior efficacy of perindopril/amlodipine 3.5/2.5 mg in comparison with placebo and monocomponents amlodipine 2.5 mg, perindopril 3.5 mg and 5 mg, and non-inferiority with amlodipine 5 mg, after 8 weeks. The superiority of perindopril/amlodipine 14/10 mg in comparison with monocomponents amlodipine 10 mg and perindopril tert-butylamine 16 mg, after 6 weeks. The proportion of patients with controlled blood pressure increased significantly after each dose of the perindopril/amlodipine strategy, At 3 months, the perindopril/amlodipine strategy produced greater reduction in blood pressure and better and faster control of hypertension than the classical stepped-care valsartan ± amlodipine strategy, The data show that the single pill combination improved the benefit/risk ratio, especially considering a 67% reduction in calcium channel blocker dose-related peripheral edema at the first step (perindopril 3.5 mg / amlodipine 2.5 mg) and a 42% reduction at last step (perindopril 14 mg/amlodipine 10 mg), without unexpected adverse events or any new safety signal. Conclusions: This registration development is among the largest of the past decade in hypertension. This single-pill combination strategy was effective and safe in first-line treatment, including grade I hypertension.